Activating Students to Speak English Through Small Group Discussion - Umar, Umar; Sultan, Sultan (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The objective of this research was to describe the result of using Small Group Discussion to activate the students to speak English. The method of this research was descriptive method. It aimed at describing whether or not the use of small group discussion activates the students to speak English. It employed two kinds of instruments: they were observation checklist and questionnaire. The sample was purposive sampling considering that class III Accounting 1 of nine classes namely: III AK 1, III AK 2, III AK 3, III SEK 1, III SEK 2, III SEK 3, III KOP 1, III KOP 2, and III PEN chosen. The sample consisted of 30 students taken from the third year students of Accounting Department of SMK Negeri 1 Bulukumba Academic year 2005/2006. The data collected were analyzed in mean score. To find out the significant result of the use of small group discussion, the researcher applied Likert’s attitude scale using percentage technique. The result of data analysis shows that the use of small group discussion activates the third year students of Accounting Department of SMK Negeri 1 Bulukumba to speak English. The students have positive attitude toward teaching speaking through small group discussion technique. The mean score of the students’ attitude from 20 statements was 82.73. In other words, the students have positive attitude toward teaching speaking through small group discussion.Keywords: activate student speaking, small group discussion